Effects and Changes on Voice After Rhinoplasty: A Long-Term Report. Issue 3 (August 2019) - Guarro, Giuseppe; Brunelli, Francesco; Rasile, Barbara; Alfano, Carmine
Introduction: Vocal changes after rhinoplasty have been poorly investigated, although this surgical procedure is nowadays one of the most requested. The production of voice largely depends on the anatomy and the size of the pyramid and the nasal cavity. The authors report 51 cases of both closed and open rhinoplasty and propose a 2-year report to analyze potential effective changes on voice. Materials and Methods: Fifty-one patients were enrolled and evaluated from September of 2012 to January of 2018. All patients were studied before and 2 years after surgery. Vocal changes were assessed with an objective and a subjective evaluation. The first one allowed to perform the measurement of the intensity and frequency of vowel sound ("a") and nasal consonant sounds ("n" and "m"). For the subjective evaluation, our modified version of Voice Handicap Index Score allowed us to evaluate every single characteristic of the personal perception of voice. Results: The objective evaluation showed an increased frequency of production of the consonant sounds in 62% of cases and an increased frequency of production of the vowel sound in 68% of cases. The subjective evaluation allowed us to notice significant changes after surgery ( P = .044). No significant differences were noticed between closed and open approach. Conclusion: Reduction rhinoplasty technique proved to induce several alterations on vocal pattern. The surgeon should always inform patients about the potential effects on the voice, particularly when such changes may produce influences on the working life.